Ecological Problems Associated with the Aral Sea in Geophysical Forecasting Education - Umatkulov Ilxomjon; Jo‘rayev Adxam; Karimov Abror (Peerian Journals Publishing, 2022)
Today, the Aral Sea is viewed as a global issue. This global warming requires geographical forecasting to see what ecological consequences it will have in the future.
Keywords: Mediterranean Sea; Aral Sea tragedy; United Nations; Central Asia